Perioperative Management of Anticoagulation—Review of Latest Evidence. (March 2016) - Kannan, Arun; Poongkunran, Chithra; Shenoy, Sundeep; Abidov, Aiden
Abstract : Periprocedural anticoagulation bridging is recommended to reduce the risk of thromboembolic events in patients at a higher risk of developing thromboembolism during the perioperative period. The optimal periprocedural anticoagulation strategy has not been established. Unfractionated heparin and low molecular heparin are used in preventing thromboembolism in the special population. Novel oral anticoagulants that directly inhibit thrombin (dabigatran) or factor Xa (rivaroxaban, apixaban) are shown as effective anticoagulants in preventing thromboembolism (venous thromboembolism) in various medical conditions. They have the advantage of having a faster onset, shorter half-lives, easier monitoring, and predicable doses. But there are disadvantages to newer anticoagulants such as the unavailability of definitive reversal agents and lack of data in patients with renal insufficiency. We review the latest evidence on the effects of newer oral anticoagulants in preventing thromboembolism and its bleeding risks.